Advanced Stage at Diagnosis and Elevated Mortality among HIV-infected US Cancer Patients in the National Cancer Database - Coghill, Anna E. (Cancer, 2019)
BACKGROUND. People living with HIV (PLWH) are at increased risk for developing several cancers, but less is known about how HIV impacts the rate of progression to advanced cancer or death. METHODS. We compared stage at presentation and mortality after diagnosis between 14,453 PLWH and 6,368,126 HIV-uninfected patients diagnosed with cancers of the oral cavity, stomach, colorectum, anus, liver, pancreas, lung, female breast, cervix, prostate, bladder, kidney, thyroid, and melanoma using data from the National Cancer Database (2004–2014). Polytomous logistic regression and Cox proportional hazards regression were used to evaluate the association between HIV, cancer stage, and stage-adjusted mortality following diagnosis, respectively. Regression models accounted for the type health facility where cancer treatment was administered and type of individual health insurance. RESULTS. HIV-infected cancer patients were more likely to be uninsured (HIV-infected: 5·0% vs. HIV-uninfected: 3·3%; P<0·0001) and were less likely to have private health insurance (25·4% vs. 44·7%; P<0·0001). Compared to non-PLWH, the odds of being diagnosed at advanced stage were significantly elevated in PLWH for melanoma and cancers of the oral cavity, liver, female breast, prostate, and thyroid (OR for stage IV vs. stage I range:1·24–2·06). PLWH diagnosed with Stage I-III disease experienced elevated mortality following diagnosis across 13 of the 14 cancer sites evaluated, with hazard ratios ranging from 1·20 (95%CI 1·14–1·26) for lung cancer to 1·85 (1·68–2·04), 1·85 (1·51–2·27), and 2·93 (2·08–4·13) for female breast, cervix, and thyroid cancers, respectively. CONCLUSION. PLWH were more likely to be diagnosed with advanced-stage cancers and to experience elevated mortality following cancer diagnosis, even after accounting for healthcare-related factors.